Pengaruh Penggunaan Aplikasi Fintech, Literasi Keuangan, Lingkungan Sosial, Dan Pengendalian Diri Terhadap Pembelian Impulsif Mahasiswa Generasi Z Di Universitas Muhammadiyah Surakarta - Naufal Hafidh Febrian; Sitti Retno Faridatussalam (Yayasan Riset dan Pengembangan Intelektual, 2026)
The rapid development of financial technology (fintech) has transformed consumer behavior, particularly among Generation Z university students who exhibit a high level of digital technology adoption. The convenience of fintech applications may increase impulsive buying behavior, which is also influenced by financial literacy, social environment, and self-control. This study aims to examine the effects of fintech application usage, financial literacy, social environment, and self-control on impulsive buying behavior among Generation Z students at Universitas Muhammadiyah Surakarta. This research employed a quantitative approach with a causal associative design. A total of 300 respondents were selected using purposive sampling. Data were collected through an online questionnaire using a Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The findings indicate that all constructs satisfied validity and reliability requirements. The coefficient of determination (R²) was 0.515, indicating that the proposed model explained 51.5% of the variance in impulsive buying behavior. Hypothesis testing revealed that fintech application usage (β = 0.598; p < 0.001), financial literacy (β = 0.100; p = 0.034), social environment (β = 0.186; p < 0.001), and self-control (β = 0.136; p = 0.004) had positive and significant effects on impulsive buying behavior. Fintech application usage was identified as the most dominant predictor. These findings suggest that the convenience of digital financial technology is the primary driver of impulsive buying among Generation Z students. Therefore, strengthening financial literacy accompanied by improved self-control and responsible fintech utilization is essential.